EKSISTENSI KESETARAAN GENDER DI RUANG PUBLIK DALAM PERSPEKTIF ISLAM - Haidar Aroya, Muhammad Parhan, Rohatul Islamiah, Sofia Nurrahma, Sulthon Esa Nur Wakhid, (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2024)
This research discusses the existence of gender equality in public spaces from an Islamic perspective. Gender issues from an Islamic perspective are increasingly attracting the interest of many people. Islam is a religion that upholds the values of justice and equality. On earth, men and women are equal as servants and caliphs. Men and women have the potential to have the same position and achieve optimal performance. The aim of this research is to explore and analyze the concepts of gender equality and how gender equality is implemented in public spaces, especially by considering Islamic principles. The method used in this research uses a qualitative method using a case study approach and literature study. The results of this research show that Islam recognizes the existence of gender equality in the public sphere, however, in its implementation there are still things that hinder gender equality, namely the existence of a crisis in society's mindset about gender, institutional policies that only benefit one party, and the many cases of gender discrimination. in public spaces.